2017
DOI: 10.1186/s12947-017-0110-y
|View full text |Cite
|
Sign up to set email alerts
|

Carotid plaque rather than intima-media thickness as a predictor of recurrent vascular events in patients with acute ischemic stroke

Abstract: BackgroundTo investigate the impacts of carotid plaque and intima-media thickness (IMT) on future vascular events (VEs) in the patients with acute ischemic stroke.MethodsA total of 479 consecutive Korean patients with acute ischemic stroke were divided into 2 groups according to development of VEs; VE group (65.4 ± 10.9 years) vs no VE group (62.8 ± 13.2 years). VEs were defined as the development of recurrent stroke, coronary events, peripheral arterial disease, and death. Clinical, laboratory, and imaging fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…10,11,13 Additionally, carotid imaging further identifies advanced stages of atherosclerosis, such as plaques and stenosis, either in the absence of or concurrent with diffuse carotid thickening. 14,17 Moreover, PWV measurement is the most appropriate method to assess arterial stiffness, 18,19 and the identification of increased PWV improves risk discrimination of the first cardiovascular event. 14 Increased CIMT is an independent, strong predictor of future vascular events, 11,15,16 while carotid plaques independently predict cardiac events and CVD recurrence in patients who have had an ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,13 Additionally, carotid imaging further identifies advanced stages of atherosclerosis, such as plaques and stenosis, either in the absence of or concurrent with diffuse carotid thickening. 14,17 Moreover, PWV measurement is the most appropriate method to assess arterial stiffness, 18,19 and the identification of increased PWV improves risk discrimination of the first cardiovascular event. 14 Increased CIMT is an independent, strong predictor of future vascular events, 11,15,16 while carotid plaques independently predict cardiac events and CVD recurrence in patients who have had an ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…14 Increased CIMT is an independent, strong predictor of future vascular events, 11,15,16 while carotid plaques independently predict cardiac events and CVD recurrence in patients who have had an ischemic stroke. 14,17 Moreover, PWV measurement is the most appropriate method to assess arterial stiffness, 18,19 and the identification of increased PWV improves risk discrimination of the first cardiovascular event. 6,18 However, the relationship between migraine and arterial stiffening [20][21][22][23][24] or carotid artery disease 20,[23][24][25][26][27][28][29][30][31][32][33][34][35] is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, plaque assessment in addition to CIMT should be considered in CV risk prediction. Several articles have shown that the assessment of carotid plaque (e.g., presence/absence of plaque, plaque thickness, plaque area or plaque score) is more useful than CIMT for predicting future CVD. Furthermore, considering not only the largest identified plaque, but also the total plaque burden in both carotid arteries might further improve risk estimation.…”
Section: What Kind Of Carotid Ultrasound Parameters Should Be Measured?mentioning
confidence: 99%
“…[9][10][11][12][13] The association between CCA-IMT and risk or prediction of stroke has been questioned. [13][14][15][16] The present meta-analysis was aimed to clarify the association of CCA-IMT with risk of stroke and its subtypes by estimating pooled analysis of published literature.…”
Section: Introductionmentioning
confidence: 99%